Identification of the Use of Noni Leaf Extract (Morinda Citrifolia) in Blood Observations in Gouramy Fish (Osphronemus Gouramy) Infected with Aeromonas Hydrophila - Yora Utami; Nurkholifah Dwi Rahayu; Fajar Rudy Hartono (Universitas Islam Lamongan, 2024)
Aeromonas hydrophila is a facultative anaerobic bacteria, namely bacteria that can grow in conditions with or without oxygen. One of the diseases that fish farmers fear is red spot disease or Motile Aeromonas Septicemia (MAS) which is caused by A. hydrophila. Therefore, it is necessary to use alternative materials that can be used to eliminate A. hydrophila, one of which is by using herbal medicines. A natural ingredient that can be used to treat fish attacked by bacteria is noni leaves (Morinda citrifolia). The aim of this research was to determine the active compound content in noni leaf extract (M. citrifolia) and the use of noni leaf extract (M. citrifolia) on the hematology of gouramy fish. The results of the Column Chromatography (KK) test showed that the crude extract of noni leaves was positive for alkaloids, saponins, triterpemoids and flavonoids. And in the GC-MS test, it was discovered that the most dominant phenolic compounds contained in noni leaf extract. The results of hemotological data analysis based on the ANOVA test showed that administration of noni leaf extract (M. citrifolia) had a significant effect (p<0.05) on hematocrit, erythrocytes, leukocytes and hemoglobin. Based on the results of observations of the parameters seen, treatment of gouramy fish (Osphronemus gouramy) infected with A. hydrophila bacteria at an optimal dose of 360 ppm.